Effects of Assistive Home Technology on quality of life and falls of people with dementia and job satisfaction of caregivers: Results from a pilot randomized controlled trial. Issue 5 (2nd September 2020) - Lauriks, Steve; Meiland, Franka; Osté, Johan P.; Hertogh, Cees; Dröes, Rose-Marie
ABSTRACT: Objectives: Determine the effects of the implementation of Assistive Home Technology (AHT) in group homes on the quality of life (QoL) of people with dementia and on job satisfaction of caregivers. Method: Pilot randomized controlled trial in nine in-patient care group homes (group homes with vs. without AHT). Participants were 54 people with dementia and 25 professionals. Outcome measurements were QoL, fall incidents, needs, use of restraints, job satisfaction, workload, and general health. Results: Living in a group home with AHT had a positive effect on four QoL domains: 'social isolation', 'having things to do', 'esthetics', and 'quality of life appreciation'. No effects were found on 12 other QoL domains. Fall incidents during bathroom visits were significantly reduced by the application of AHT. During this implementation phase, in the AHT group home, a moderate negative effect was found on caregiver's appreciation of work circumstances. No effects on other outcome measures were found. Conclusion: Positive effects were found on aspects of QoL and fall incidents in the bathroom. The lower caregiver appreciation of work circumstances in the AHT group confirms the importance of intensive support and guidance of personnel during the implementation of AHT.